Listeria monocytogenes in renal transplant recipients - Cristina Barroso HOFER; Carmo Elias Andrade MELLES; Ernesto HOFER (Revista do Instituto de Medicina Tropical de São Paulo, 1999)
Five cases of Listeria monocytogenes bacteriemia were observed from April to December 1985, among renal transplant recipients from the same hospital in São Paulo, Brazil. The patients were adults (mean age: 40.6 years), and the basic complain was fever, with no report of meningeal syndrome. Laboratory tests revealed the presence of two serovars, 1/2a and 4b, which were classified into three lysotypes. The four strains of serovar 4b showed the same antibiotype, with resistance to cefoxitin, clindamycin, oxacillin and penicillin.